Use of a Large Group for Discussion and Review of Medical Physiology: Applied Renal Physiology - Rob Zachow; Ross Goldstein (Association of American Medical Colleges, 2008)
Abstract Introduction Through our experience with the medical physiology course at Robert Wood Johnson Medical School (RWJMS), we recognized the need for an application-based review process for first-year medical and physician assistant students designed to provide self-evaluation of the knowledge base. As a result we created a series of interactive reviews for the entire class using the format more traditionally used in a small-group setting. This review focuses on applied renal physiology. Other reviews in the series focus on atrial fibrillation and cardiovascular medicine. Methods Short clinical vignettes with discussion topics were developed and presented to the entire class (approximately 210 students) using a PowerPoint-based lecture format. Following the case presentation, the class was challenged with discussion topics and questions which could be solved using the level of understanding of medical physiology principles as presented in the preceding unit lectures, and through self-directed learning using suggested readings. Facilitation is guided by personnel with expertise of the subject matter. Results The renal discussion was piloted as a component of the RWJMS medical physiology course in 2007. Based on feedback obtained through anonymous student course block surveys, the students found this approach a beneficial use of course time. Students further indicated that the use of clinical vignettes demonstrated the importance of integrative thinking in order to fully comprehend and more fully appreciate the importance of the preclinical curriculum (e.g., medical physiology) as it applies to the clinical experience. Discussion Through this method, students could self-evaluate their knowledge base within a particular medical physiology system following the end-of-lecture series and prior to the block examination. We believed that this checkpoint assisted in emphasizing key concepts while promoting integrative thinking and problem-solving skills. The overall goal of this approach was to demonstrate to the students the importance of integrative thinking as a better learning technique as compared to rote memorization methods.